C6- and C7-Substituted 3,4-dihydro-2(1H)-quinolinones as Inhibitors of Monoamine Oxidase - Meiring, Letitia; Petzer, Jacobus Petrus; Petzer, Anél (Drug Research, 2017)
Purpose Monoamine oxidase (MAO) inhibitors are considered to be useful therapeutic agents and isoform specific inhibitors are employed for the treatment of depression and Parkinson’s disease. MAO inhibitors are also under investigation for the treatment of disorders ranging from Alzheimer’s disease, prostate cancer and certain cardiomyopathies. While a number of irreversible MAO inhibitors are available in the clinic, reversible inhibitors, particularly of the MAO-B isoform are still being developed. Based on our interest in discovering reversible inhibitors with specificity for MAO-B, we have recently reported that, among a series of 10 3,4-dihydro-2(1H)-quinolinone derivatives, are high potency MAO-B inhibitors, with a number of homologues displaying good selectivities for MAO-B over the MAO-A isoform.Methods and Findings: To expand on these promising findings and to derive structure-activity relationships, the current study synthesizes a series of 14 3,4-dihydro-2(1H)-quinolinone derivatives. An evaluation of their MAO inhibition properties shows that all derivatives are MAO-B specific with the most potent inhibitor (3a) displaying an IC50 value of 0.0014 µM. Selectivities for MAO-B ranged from 99 to 40 000-fold.Conclusions: It may thus be concluded that substitution of 3,4-dihydro-2(1H)-quinolinone on C6 and C7 with a variety of side chains yields highly potent and selective MAO-B inhibitors, compounds with existing and prospective therapeutic applications.